PROTEST LOKALNY W POLSCE - Matczak, Piotr (Wydział Prawa i Administracji UAM, 2000)
Issuing from polish and foreign literature of the subject the Author discusses a comprehension of a protestation and explains this phenomenon in the light and context of consolidation process of democracy itself. Next the reasons and a set of specific features of such local protestations (as well as o f the so-called micro-protestations) in Poland are debated in Details. The Author focuses also on a protestation seen an element of civic society and on essential points of local protestation involved with redistributing common goods.
PROTESTATION OF LOCAL NATURE IN POLAND